Initial leak pressures of four anastomosis techniques in cooled cadaveric canine jejunum. Issue 3 (8th February 2020) - Fealey, Mark J.; Regier, Penny J.; Steadman BS, Charles; Brad Case, J.; Garcia‐Pereira, Fernando
Abstract: Objective: To compare the effectiveness of four different intestinal anastomosis techniques at preventing leakage after enterectomy. Study design: Experimental study. Sample population: Grossly normal jejunal segments (N = 70) from three fresh canine cadavers. Methods: Eight‐centimeter cooled canine cadaveric jejunal segments were randomly assigned to a control group (six segments) and four treatment groups (16 segments each [two segments/anastomotic construct]): (1) handsewn anastomosis (HSA), (2) barbed suture anastomosis (B‐HSA), (3) stapled functional end‐to‐end anastomosis (SFEEA), and (4) stapled functional end‐to‐end anastomosis with an oversew (SFEEA‐O). Control segments and anastomotic constructs were infused intraluminally to the point of leakage. Initial leak pressures were recorded and compared. Results: Initial leak pressures (median + range) for jejunal control segments, HSA, B‐HSA, SFEEA, and SFEEA‐O were 331.88 mmHg (range, 315.34–346.64), 35.17 (20.29–56.24), 24.99 (6.08–38.64), 28.77 (18.80–85.09), and 35.92 (12.05–80.71), respectively. No difference was detected between leak pressures of anastomosed segments ( P = .35), all of which were more variable and lower than those of intact segments. Conclusion: No difference in initial leak pressures was detected between the four anastomosis techniques tested in cooled canine cadaveric jejunum. Clinical significance: All four anastomosis techniques evaluated in this study may be suitable in dogs.